Remove the brackets
-5a + 9b + 7a combine -5a and 7a
7a - 5a + 9b
2a + 9b Answer
Don't go any further. There is nothing else to do. These are unlike terms and cannot be reduced or combined.
Answer:
Step-by-step explanation:
Show that if 3x – 7 = 5, then x = 4.
Here, our given statement is 3x – 7 = 5, and we're asked to prove x = 4.
x=4
Statements Reasons
1. 3x – 7 = 5 Given
2. 3x – 7 + 7 = 5 + 7 Addition of 7 to equation (1)
3. 3x + 0 = 5 + 7 Substitution of –7 + 7 = 0 into (2)
4. 3x = 5 + 7 Substitution of 3x + 0 = 3x into (3)
5. 3x = 12 Substitution of 5 + 7 = 12 into (4)
6. 3x⁄3 = 12⁄3 Dividing equation (5) by 3
7. x = 12⁄3 Substitution of 3x⁄3 = x into (6)
8. x = 4 Substitution of 12⁄3 = 4 into (7)
Is there such a thing as being too descriptive? Yep, and that was it, since over half the proof was devoted to telling the reader how to do arithmetic. We'll typically take numerical computation for granted, and write proofs like this:
Answer:
3.2
Step-by-step explanation:
11.5 - 5.1 = 6.4
6.4 ÷ 2 = 3.2